Contact Dermatitis in Nail Cosmetics - Zoe M. Lipman; Antonella Tosti (Allergies, 2021)
Many ingredients found within nail cosmetic products are capable of sensitizing patients’ immune systems and causing contact dermatitis (CD). These include but are not limited to tosylamide, (meth)acrylates, and formaldehyde. A clear temporal relationship between nail cosmetic procedures and an eczematous outbreak on the hands, face, or other ectopic body regions can be a key indicator of CD secondary to nail cosmetic exposure. Once an inciting allergen is identified through patch testing, elimination and avoidance becomes a mainstay of treatment alongside the use of emollients and topical anti-inflammatory therapies. Patients should be counselled to approach future nail cosmetic products and procedures with caution and careful attention to ingredients, regardless of whether or not it has a “hypoallergenic” label.